ANTIOXIDANT ACTIVITY TEST OF TURI (Sesbania grandiflora L.) LEAF EXTRACT USING β-CAROTENE BLEACHING METHOD - Lutfiah, Salsabilah (UNIVERSITAS MUSLIM INDONESIA, 2024)
Turi Leaf (Sesbania grandiflora L.) belong to the fabaceae family that contain flavonoids as an antioxidants. The antioxidants have free radical scavenging properties that can inhibit the oxidation of free radicals. It is used to protect the skin from oxidative damage and to prevent premature aging. This research aimed to determine the antioxidant activity of turi leaf extract by b-carotene bleaching method. The leaves were extracted using macerations method, the yield percentage of 16,685 %. Quantitative analysis by UV-Vis spectrophotometry at the maximum wavelength of 538 nm. The results showed that the antioxidant activity of the turi leaf extract is 50.7% which is intermediate antioxidant, then in quercetin standard solution. Keywords : Turi Leaves (Sesbania grandiflora L.), Antioxidant, β-carotene bleaching, UV-Vis spectrophotometry